pH, dilution and alcohol concentr ations of IBA in Ficus carica rooting - Monroy González, Isai; Villegas Monter, Angel; Peña Valdivia, Cecilia Beatriz; Barrientos Priego, Alejandro F.; Ruiz Posadas, Lucero del Mar; Castro Garibay, Sandra Luz (Revista Mexicana de Ciencias Agrícolas, 2024)
Vegetative propagation with stem cuttings requires the origination of shoots and roots to form a complete plant. Factors involved in root generation have been researched, but little work has been done on pH. The research was conducted at the College of Postgraduates, Montecillo Campus, Texcoco, Mexico in 2021. In Ficus carica cuttings, the following were evaluated: pH values (4, 7, and 11) in solution with or without auxin, dilution (alcohol or NaOH) of indole butyric acid (IBA), concentration of alcohol to dissolve IBA (10, 15, and 20%), in the percentage of rooting, number of roots, length of the longest root, percentage of sprouted buds at 21 days, date of establishment and anatomical changes at 0, 3 and 6 days after the cutting. Meristematic cells and root primordia were found up to day 6. One hundred percent rooting was obtained in all treatments. pH was not shown to have an effect on the auxin solution, but it did influence the percentage of rooting assessed individually. The way auxin was diluted influenced the number of roots due to the concentration of alcohol used, lower concentration (10%) had a positive effect.